Pregnancy after embolization for arteriovenous malformation: an uncommon successful outcome - Javed, Arshia; Sana Sheikh (Journal of the Pakistan Medical Association, 2020)
Uterine arteriovenous malformation (AVM) is an uncommon but fatal condition and cause bleeding from abnormal connection between artery and vein. Pregnancy after embolization of uterine AVM is very uncommon, and there are increased risks of spontaneous abortion and growth retardation. We report a case of pregnancy after bilateral uterine artery embolization for AVM and its successful outcome. Keywords: Uterine artery embolization, conception, Continuous...